2021
DOI: 10.30574/gjeta.2021.6.2.0027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the challenges and benefits associated with resource planning and leveling in the Kenyan Construction Industry

Abstract: Resource Planning and Leveling are two critical areas of resource management which need to be implemented by contractors to aid in construction project execution. However, in the process of undertaking these processes in their projects, contractors meet a number of challenges which discourage them from implementing Resource Planning and Leveling. Nonetheless, Resource Planning and Leveling has a number of benefits which may not be known by some contractors. The purpose of this research therefore was to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
0
0
Order By: Relevance
“…This means that identification of resources leads to better estimation of the resources and vice versa. This agrees with Shadrack (2018) study that discovered that even though resource identification in the industry was used to a great extent, much of it was non-structured. Li et al (2008) study revealed that resource estimation was fundamental in providing project estimates that were effective besides enhancing efficiency in using project resources.…”
Section: Regression Analysissupporting
confidence: 90%
“…This means that identification of resources leads to better estimation of the resources and vice versa. This agrees with Shadrack (2018) study that discovered that even though resource identification in the industry was used to a great extent, much of it was non-structured. Li et al (2008) study revealed that resource estimation was fundamental in providing project estimates that were effective besides enhancing efficiency in using project resources.…”
Section: Regression Analysissupporting
confidence: 90%
“…This statement was strongly agreed by 16.9% of the respondents, 62.0% agreed, 11.3% neutral, 5.6% disagreed and 4.2% strongly disagreed. This is in agreement with a research by Shadrack (2018) on issues affecting practices of planning of resources in the construction sector within Kenya with a shift to contractors of the county of Nairobi and discovered that even though resource planning in the industry was used to a great extent, much of it was nonstructured.…”
Section: Resource Planningsupporting
confidence: 87%